Asymptotic inference in poverty indices: an empirical processes approach. Issue 12 (18th June 2017) - Seck, Cheikh Tidiane; Ngatchou-Wandji, Joseph; Lô, Gane Samb
ABSTRACT: We derive an empirical poverty index containing most of those proposed in the literature. Then, we study its asymptotic behavior by using empirical processes theory. From the results obtained, we derive a Wald-type test for comparing a vector of theoretical poverty indices to a vector of reference indices. We study the test statistic under the null hypothesis of equality, fixed alternatives, and a sequence of local alternatives. A simulation experiment conducted shows that our test performs well for exponential and Pareto data.